Peningkatan Kualitas UMKM di Ekowisata Bale Mangrove melalui Kelas Bahasa Inggris - Hidayat, Sugih Akbar; Oktaviani, Nur Padia; Yuliana, Baiq Fadilla; Ardani, Sarwan; Hatami, Muhamad; Ramdani, Novia; Syukur, Abdul; Handayani, Baiq Sri; Sukma, Izza Melati (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Bale Mangrove ecotourism in Poton Bako Hamlet, Jerowaru Village, East Lombok, attracts domestic and international tourists, opening up opportunities for MSME players to expand their markets. However, limited English language skills among MSME actors hinder effective interaction with foreign tourists. This study aims to improve the English language skills of MSME actors through English language training that focuses on tourism communication and English-based menu creation. The program, which was implemented between July and October 2024, showed an increase in English language skills among participants, as well as success in creating English menus that facilitate interaction with foreign tourists. This program increases the competency of MSME players in serving international tourists and supports the development of Bale Mangrove Ecotourism as a sustainable destination.